PENGELOLAAN OBJEK WISATA TAMAN HUTAN RAYA BUNG HATTA KOTA PADANG - FASANDRA, FERNANDO; Yuliana, Yuliana; Suyuthie, Hijriyantomi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
The research is motivated by the conditions of the Bung Hatta Forest Park is not maintained properly. The purpose of research is to describe the Management of Forest Park Attraction Bung Hatta Padang City which includes: planning, organizing, actuating, controlling. The research is descriptive qualitative, with the sources of data that was taken from management officer informants, local communities, and visitors. Selection of the informants using snowball sampling technique. Data collection is using interview technique, observation, and documentation. The results of research indicates that the Management of Forest Park Attraction Bung Hatta Padang City is not maximized. This can be seen by each indicator: (1) The planning attraction for the long term is to conservate the area and for the short term is to development attraction. The planning in general has not led to the development of the attraction, (2) The organizing of the management officers is only responsible about main duties of technical operations and technical support, and application of the organizing management are still in general, with lack of specification of work, (3) actuating was remind to each other from management officers attraction for the jobs to be done, (4) The controlling was conduct by management officers together with the local communities of attraction, police, and Padang City forestry agency.